Simple correction to bandgap problems in IV and III–V semiconductors: an improved, local first-principles density functional theory. (11th September 2019) - Datta, Sujoy; Singh, Prashant; Chaudhuri, Chhanda B; Jana, Debnarayan; Harbola, Manoj K; Johnson, Duane D; Mookerjee, Abhijit
Abstract: We report results from a fast, efficient, and first-principles full-potential N th-order muffin-tin orbital (FP-NMTO) method combined with van Leeuwen–Baerends correction to local density exchange-correlation potential. We show that more complete and compact basis set is critical in improving the electronic and structural properties. We exemplify the self-consistent FP-NMTO calculations on group IV and III–V semiconductors. Notably, predicted bandgaps, lattice constants, and bulk moduli are in good agreement with experiments (e.g. we find for Ge 0.86 eV, 5.57, 75 GPa versus measured 0.74 eV, 5.66, 77.2 GPa). We also showcase its application to the electronic properties of 2-dimensional h -BN and h -SiC, again finding good agreement with experiments.